The role of architecture on urban revitalisation: The case of olympic arenas in Berlin-Prenzlauer Berg. - Ahlfeldt, P. Gabriel M.; Maennig, Wolfgang (My University, 2007)
Das Papier untersucht die soziökonomischen Auswirkungen der im Rahmen der Olympiabewerbung Berlins gebauten multifunktionalen Sporthallen in Prenzlauer Berg. Als Untersuchungsgegenstand ausgewählt wurden die Max-Schmeling-Arena und das Velodrom wegen ihres Potenzials zur Revitalisierung und Aufwertung des sie umgebenden vernachlässigten Stadtquartiers. Für die Auswertung der Daten wurde ein difference-in-differences-Ansatz gewählt, um nach strukturellen Brüchen in der Entwicklung der Bodenwerte im jeweiligen Stadtquartier zu suchen. Die Ergebnisse zeigen, dass von den Stadionbauten externe Effekte ausgehen, die offensichtlich den Prozess der Gentrifizierung des Prenzlauer Bergs beschleunigt haben.

Thre paper investigates socioeconomic impacts of multifunctional sports arenas situated in Berlin-Prenzlauer Berg, Germany. The three arenas were chosen for their potential to contribute to revitalisation of their economically deprived neighbourhoods. We employ a difference-in-differences approach to check for structural breaks in development of land values within areas of potential impact. Our results suggest that arenas emanate positive externalities and apparently have accelerated the process of gentrification going on in Prenzlauer Berg. However, evidence also supports concerns that congestion problems may adversely affect property values, at least when not addressed appropriately during planning.
Keywords: Stadtentwicklungsplanung; Stadtteil; Revitalisierung; Sportstätte; Bodenwert; Bodenpreis; Aufwertung; Immobilienmarkt; Gentrification; Externe Effekte